Metabolites from the soft coral -associated bacterium \(Micrococcus\) sp. strain a-2-28 - Pham , Thi Mien; Wiese, Jutta; Dao Viet Ha, Dao Viet Ha (Vietnam Journal of Marine Science and Technology, 2023)
The marine actinomyces Micrococcus was the most common bacterium among the isolates corals, sponges, and alga isolates. Only a few investigations of natural compounds from Micrococcus sp. were reported previously. This study implicated the soft coral-associated Micrococcus sp. strain A-2-28 (following relative Micrococcus flavus LW4T) for large-scale cultivation, chemical analyses, and biological activities. Whereas crude extract of the strain A-2-28 inhibited only Staphylococcus epidermidis, metabolites profiles and pure compounds from strain A-2-28 showed that this strain produced phytohormone (IAA), metabolized some new compounds which were almost inactive for biological tests. This work suggested that it is possible to plan a new strategy for improving coral health and resilience though their associated microbial.